Pengaruh Perputaran Kas, Perputaran Piutang, Perputaran Persediaan, Current Ratio, dan Debt to Equity Ratio, Total Assets Turn Over terhadap Profitabilitas: Studi Kasus pada Sektor Industri Dasar dan Kimia - Hantono Hantono; Siti Tiffany Guci; Eva Mariana Boang Manalu; Novi Agusniawati Hondro; Cindy Claudia Manihuruk; Meilianta Br Perangin- Angin; Desy Christiana Sinaga (Politeknik Ganesha Medan, 2019)
The purpose of this research is to examine the effect of the cash turnover, receivable turnover, inventory turnover, current ratio, debt to equity ratio, and total assets turn over to profitability. This Research was conducted on basic and chemical industry manufacturing companies listed in Indonesia Stock Exchange period 2013-2017. The methods of analysis using multiple regression analysis. The analysis method used is multiple linear regression, F test, and T-test. The result of this analysis showed that profitability was influenced simultaneously by cash turnover, receivable turnover, inventory turnover, current ratio, debt to equity ratio and total assets turn over. Meanwhile on partial analysis showed only receivable turnover and inventory turnover, current ratio, debt to equity ratio and total assets turn over hasn’t influence to profitability.